Strong interaction effects in scalar top production - Drees, M.; Éboli, O. J P [UNESP] (Elsevier, 2000)
We discuss effects of fragmentation and hard gluon radiation on the signal for the pair production of the lighter scalar top eigenstate t̃1 at e+e- colliders. The main emphasis is on scenarios with small stop-LSP mass splitting, where strong interaction effects can considerably modify kinematical properties of the final state.